Preparation method and detection method of modified polyisocyanate adhesive with long storage period

The preparation and detection methods enhance Lekna glue's storage period and performance by color change treatment and homogenization, addressing issues of short storage and inadequate detection, resulting in improved bonding strength and viscosity.

CN119193080APending Publication Date: 2024-12-27LIAONING HONGSHAN CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411314727.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Lekna glue suffers from short storage period, low bonding strength, sensitivity to water vapor, and inadequate detection methods that fail to reflect actual product performance, particularly in bonding strength, viscosity, and initial adhesion.

Method used

A preparation method involving color change treatment with LED irradiation and homogenization with a modifier, along with detection methods that simulate bonding conditions and environmental humidity, to enhance storage period and performance indicators.

Benefits of technology

The method extends the storage period to 18 months, improves bonding strength, viscosity, and water resistance, and provides a more accurate detection method for Lekna glue performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a preparation and detection method of a modified polyisocyanate adhesive with a long storage period. The preparation method comprises the following steps: S1, discoloring the polyisocyanate adhesive; s2, preparing a modifier; and S3, preparing the modified polyisocyanate adhesive. According to the invention, the modifier is added into the discolored polyisocyanate adhesive, so that the viscosity of the product is improved by 2.3-16.6 times, the saturated water absorption rate is reduced by 1.5-8.3%, and the acid value is reduced by 13-60%. According to the present invention, the original yellow and green color of the modified polyisocyanate adhesive is changed into the red purple color by using the illumination method, and the storage period of the modified polyisocyanate adhesive is prolonged through the color changing treatment and the addition of the modifier, such that the storage period of the modified product can still achieve 18 months so as to conform to the shelf life of the polyisocyanate adhesive product. The method is simple, convenient, efficient, low in cost and high in efficiency. The invention further provides a detection method which is more scientific, more visual and closer to reality and reflects performance and quality indexes of polyisocyanate adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane adhesives, and in particular to a preparation and detection method of modified Lekena glue with a long storage period. Technical Background

[0002] Lekna glue, also known as triphenylmethane triisocyanate, is widely used in the vulcanization bonding of nitrile rubber, chloroprene rubber, natural rubber and metal. Lekna glue has the disadvantages of thin glue liquid, low viscosity, low initial viscosity, sensitive to water vapor in the use environment, and high acid value. The purpose of optimizing performance can be achieved through physical modification and chemical modification, but the modification method will affect the storage period of Lekna glue products. In the process of product sales and use, the storage period is a very important quality indicator.

[0003] Since the production of Lekna glue requires highly toxic phosgene, there are relatively few manufacturers and there are currently no national or industry standards. The applicant has been producing Lekna glue for more than 20 years and has formulated the enterprise standard Q / LHHJGJ02-2019 for the product, but it cannot meet the actual needs of users. For example, (1) the enterprise standard stipulates that the bonding strength test uses 5470 # Rubber, the bonding strength is ≥4.0MPa to be qualified, but in the actual use of customers, the tensile strength and tear strength of various types of rubber are less than 5470 # Rubber, that is, the bonding strength is ≤4.0MPa but the actual bonding effect is good, that is, the quality index of bonding strength in the enterprise standard cannot scientifically and correctly reflect the bonding effect. (2) Lekna glue has the disadvantage of thin glue liquid. The test method of GB / T2794-1995 for the determination of adhesive viscosity cannot intuitively express the viscosity performance. (3) Lekna glue is sensitive to water vapor in the use environment. The GB / T1034-2008 method for determining the water absorption of plastics cannot be close to the actual use situation.

[0004] (4) In actual use, customers of Lekna glue have requirements for initial adhesion performance. The test method of GB / T2794-1995 for the determination of adhesive viscosity cannot objectively reflect the initial adhesion performance. Summary of the invention

[0005] In view of the problems existing in the prior art, the purpose of the present invention is to provide a preparation method and a detection method of modified Lekna gum with a long storage period, so as to overcome the defect of short storage period of modified Lekna gum and make up for the deficiency that the existing Lekna gum detection method cannot satisfy customers' comprehensive understanding of product performance.

[0006] The present invention is achieved in that:

[0007] A method for preparing modified lekena gum with a long shelf life comprises the following steps:

[0008] S1. Color change treatment of Lekna glue: In a dark room without light, put yellow or green Lekna glue in a transparent narrow-necked bottle, fill the bottle with nitrogen, seal it, and let it stand. Place an LED lamp 5 cm to 10 cm away from the narrow-necked bottle, and continuously irradiate it with the LED lamp for 72 h to 78 h to change the appearance color of the Lekna glue to red-purple; move the red-purple Lekna glue out of the dark room, heat it up and stir it, and replace the acidic gas in the dry material with nitrogen at the same time, filter out the precipitate and impurities, and seal it;

[0009] S2 Preparation of modifier: Set the speed of the homogenizer to 1500r / min~2000r / min, the stirring time to 55min~60min, and homogenize the liquid nitrile rubber W2740 until there are no bubbles visible to the naked eye;

[0010] S3 preparation of modified Lekna gum: weigh the color-changing Lekna gum obtained in step S1, and put it into a homogenizer; weigh the modifier liquid nitrile rubber W2740 obtained in step S2, the mass of the modifier is 5% to 20% of the mass of the modified Lekna gum, and add the modifier dropwise into the homogenizer; set the speed of the homogenizer to 200r / min to 300r / min, and the stirring time to 160min to 180min; stir and mix thoroughly to obtain modified Lekna gum.

[0011] Preferably, when the reddish purple lekena gum treated in step S1 is heated and stirred, the material temperature is controlled between 136° C. and 140° C., kept constant for 160 min to 180 min, the heating is stopped, and the material is filtered after cooling.

[0012] A method for detecting modified lekena gum, comprising the following tests:

[0013] S1 Bond Strength Test

[0014] When using non-5470 according to Q / LHHJGJ02-2019 standard # When bonding rubber, the degree of damage to the bonding surface is used to indicate the bonding strength:

[0015] Completely destroy the bonding surface rubber damage area ≥ 80%

[0016] Destroy the bonding surface rubber damage area 50% to 80%

[0017] Incomplete destruction of the bonding surface rubber damage area 30% to 50%

[0018] The damaged area of ​​rubber on the undamaged bonding surface is ≤30%;

[0019] S2 Viscosity Test

[0020] Anti-sagging performance test: Fix a glass test tube on a slope with a scale and an angle of 20 degrees, fix a zero point at the mouth of the glass test tube, take 0.2ml of glue and drop it at the zero point of the test tube, let the glue drip down naturally, measure the dripping distance and time of the glue, and use the average flow rate to indicate the anti-sagging performance;

[0021] S3 water resistance test

[0022] Atomization test: Install a humidifier and a hygrometer in the fume hood, keep the humidity constant for 0.5 hours, and then conduct the bonding strength test in the fume hood, that is, simulate the actual humidity environment to conduct the bonding strength test. The limit humidity value when the bonding strength is ≥4.0MPa is used to represent the water resistance of the actual bonding process;

[0023] S4 initial adhesion test

[0024] Initial adhesion test: The bonding specimens are two 5470 pieces with a length of 10 cm and a width of 2.5 cm. # Rubber: clean with ethyl acetate, air-dry for 20 minutes, apply a thin layer of glue, the coating area is 10cm x 2.5cm, air-dry for 30 minutes for the first time and 40 minutes for the second time; when pressing, hit the bonding surface with a hammer three times and measure the peeling force; then quickly press, hit the bonding surface with a hammer three times and measure the re-bonding peeling force.

[0025] The present invention increases the viscosity of the product by 2.3 to 16.6 times, reduces the saturated water absorption by 1.5 to 8.3%, and reduces the acid value by 13 to 60% by adding a modifier to the discolored Lekena gum. The present invention uses a light irradiation method to change the original yellow and green color of the modified Lekena gum into reddish purple. Through the discoloration treatment and the addition of the modifier, the storage period of the modified Lekena gum is extended, and the storage period of the modified product can still reach 18 months, which meets the shelf life of the Lekena gum product. The method of the present invention is simple, efficient, low in cost, high in efficiency, and has promotion value.

[0026] The present invention provides a more scientific, more intuitive and more practical detection method for reflecting the performance and quality index of Lekna glue. By using the detection method of the present invention to detect the modified Lekna glue product with a long storage period obtained by the present invention, it can be seen that the modified Lekna glue product of the present invention has the following advantages: (1) while changing the performance of Lekna glue, it can still meet the shelf life of Lekna glue; (2) the anti-sagging performance is improved, the glue overflow phenomenon during use is reduced, and the economic value of the product is improved; (3) the viscosity of the product is improved, and the inherent disadvantage of the thin glue liquid is improved; (4) the initial adhesion performance is improved, which changes the disadvantage of the low initial viscosity of the glue liquid; (5) the water resistance is improved, and the requirements for the water vapor operating conditions in the bonding process of the glue liquid are reduced; (6) the acid value of the product is reduced, which makes up for the disadvantage of the high acid value of the glue liquid. Example

[0027] The present invention is further described below in conjunction with the embodiments. The following implementation methods of the present invention do not limit the patent protection scope of the present invention, and any equivalent structure or equivalent transformation made using the contents of the present invention specification, or directly or indirectly applied in the relevant technical field, are also included in the patent protection scope of the present invention.

[0028] Embodiment 1:

[0029] S1 Lekna Gum Discoloration Treatment:

[0030] 1.1 In a dark room without light, weigh 1000g of yellow or green Lekna glue and put it in a transparent narrow-necked bottle. Fill the bottle with nitrogen, seal it, and let it stand. Turn on the LED light placed 5cm to 10cm away from the narrow-necked bottle. Expose the LED light continuously for 72h to 78h until the appearance color of the Lekna glue changes to red-purple, and then turn off the light.

[0031] 1.2 Move the narrow-necked bottle containing the red-purple Lekna glue out of the darkroom, install it in the laboratory, start stirring, heat the material to a stable reflux, introduce nitrogen to start replacing the acid gas in the material with nitrogen, control the temperature between 136℃ and 140℃, keep the constant temperature for 160min to 180min, stop heating, and remove the acid gas in the Lekna glue;

[0032] 1.3 After the material temperature drops to room temperature, pour out the glue solution and filter it: first filter it naturally with a 10um filter cloth, then filter it with a 1um filter cloth to remove precipitation and impurities. The filtrate is the treated Lekena glue, which is transferred into a brown narrow-necked bottle and sealed for later use.

[0033] S2 Preparation of modifier: Set the speed of the homogenizer to 1500r / min~2000r / min, the stirring time to 55min~60min, weigh 100g of liquid nitrile rubber W2740, put it into the homogenizer, start the motor at room temperature and pressure, and pour the homogenized liquid nitrile rubber W2740 into a narrow-necked bottle for later use.

[0034] S3 Preparation of modified Lekena gum:

[0035] 3.1 Weigh 950g of the color-changing Lekena rubber obtained in step S1 and 50g of the modifier liquid nitrile rubber W2740 obtained in step S2 respectively, the mass of the modifier being 5% of the mass of the modified Lekena rubber.

[0036] 3.2 First, the color-changing Lekena rubber is put into a homogenizer, stirring is started, and the speed is controlled at 200r / min to 300r / min. Then, the weighed modifier liquid nitrile rubber W2740 is added dropwise into the homogenizer, and stirring is continued for 160min to 180min to fully mix the materials to obtain the finished modified Lekena rubber of the present invention.

[0037] Example 2

[0038] In step 3 of preparing the modified Lekena rubber, the treated Lekena rubber and the treated liquid nitrile rubber W2740 are weighed respectively in a mass ratio of 94:6. The other steps are the same as those in Example 1.

[0039] Example 3

[0040] In step 3 of preparing the modified Lekena rubber, the treated Lekena rubber and the treated liquid nitrile rubber W2740 are weighed respectively in a mass ratio of 92:8. The other steps are the same as those in Example 1.

[0041] Example 4

[0042] In step 3 of preparing the modified Lekena rubber, the treated Lekena rubber and the treated liquid nitrile rubber W2740 are weighed respectively in a mass ratio of 90:10. The other steps are the same as those in Example 1.

[0043] Example 5

[0044] In step 3 of preparing the modified Lekena rubber, the treated Lekena rubber and the treated liquid nitrile rubber W2740 are weighed respectively in a mass ratio of 88:12. The other steps are the same as those in Example 1.

[0045] Example 6

[0046] In step 3 of preparing the modified Lekena rubber, the treated Lekena rubber and the treated liquid nitrile rubber W2740 are weighed respectively in a mass ratio of 87:13. The other steps are the same as those in Example 1.

[0047] Example 7

[0048] In step 3 of preparing the modified Lekena rubber, the treated Lekena rubber and the treated liquid nitrile rubber W2740 are weighed respectively in a mass ratio of 85:15. The other steps are the same as those in Example 1.

[0049] Example 8

[0050] In step 3 of preparing the modified Lekena rubber, the treated Lekena rubber and the treated liquid nitrile rubber W2740 are weighed respectively in a mass ratio of 83:17. The other steps are the same as those in Example 1.

[0051] Example 9

[0052] In step 3 of preparing the modified Lekena rubber, the treated Lekena rubber and the treated liquid nitrile rubber W2740 are weighed in a mass ratio of 80:20, that is, the mass of the modifier is 20% of the mass of the modified Lekena rubber. The other steps are the same as in Example 1.

[0053] Using the standard or the detection method of the present invention, we tested and analyzed various indicators of the modified Lekena gum of the experimental product of the present invention with different proportions and the samples of the comparative experiment. Numbers 1-9 in the following data lists are Examples 1-9 of the present invention.

[0054] (1) Appearance and bonding strength

[0055] In order to verify the performance indicators of the product of the present invention, we conducted comparative experiments on 5 other materials under the same experimental conditions and using the same process mixing method.

[0056] Comparative Example 1: treated Lekna rubber: liquid nitrile rubber W33-1 = 90:10;

[0057] Comparative Example 2: treated Lekna rubber: powdered nitrile rubber P830E = 90:10;

[0058] Comparative Example 3: After treatment, Lekena rubber: neoprene = 90:10;

[0059] Comparative Example 4: treated Lekna glue: 80 mesh poplar powder = 90:10;

[0060] Comparative example 5: Lekna rubber: liquid nitrile rubber W2740 = 88:12.

[0061] Use 5470 respectively # Rubber, steel, and non-5470 # The samples were tested for bonding strength for rubber and steel. The appearance and bonding strength of the samples during storage are summarized in the following table:

[0062] Summary of appearance and bonding strength during storage period

[0063]

[0064]

[0065] Q / LHHJGJ02-2019, use 5470 # When testing rubber, the greater the bond strength value, the better; use non-5470 # When the rubber is used, a small test is conducted according to the degree of damage to the bonding surface. The larger the damage area of ​​the bonding surface, the better. The shelf life of Lekna glue is 18 months. During the storage of the modified glue solution, there is no obvious change in the properties, the bonding strength is qualified, and the degree of damage to the bonding surface reaches ≥ damage. The closer the time is to the shelf life of Lekna glue, the better. It can be seen from the test results of the embodiments and comparative examples that the glue sample prepared by the method of the present invention has an excellent storage period.

[0066] (2) Anti-sagging performance

[0067] The anti-sagging performance was tested using a self-created method, and the results are as follows:

[0068]

[0069]

[0070] The smaller the average flow rate, the better the anti-flow performance. The test results of the examples and comparative examples show that the glue sample prepared by the method of the present invention effectively improves the anti-sagging performance, with an improvement effect of about 16% to 60%.

[0071] (3) Viscosity

[0072] Referring to GB / T2794-1995 adhesive, the results of the sample viscosity test are as follows:

[0073]

[0074] The test results of the examples and comparative examples show that the viscosity of the colloid prepared by the method of the present invention is increased by 2.3 to 16.6 times.

[0075] (4) Initial adhesion performance

[0076] The test results using the self-created method are as follows:

[0077]

[0078]

[0079] The greater the initial peeling force and the re-peeling force, the better the initial adhesion performance. The test results of the examples and comparative examples show that the initial adhesion of the adhesive sample prepared by the method of the present invention is improved by 1.5 to 7 times.

[0080] (5) Water resistance

[0081] The test results using the self-created method are as follows:

[0082]

[0083] In the atomization test, when the bonding strength is ≥4.0MPa, the greater the limit humidity value, the better the water resistance; GB / T1034-2008 plastic water absorption determination, the smaller the saturated water absorption rate, the better the water resistance. Through the test results of the embodiment and the comparative example, it can be obtained that when the adhesive sample prepared by the method of the present invention has a bonding strength of ≥4.0MPa, the limit humidity value increases, the water resistance is improved by 14% to 17%, the saturated water absorption rate decreases, and the water resistance is improved by 1.5% to 8.3%.

[0084] (6) Acid value

[0085] The acid value of the sample was measured using 848 potentiometric titrator, and the test results are as follows:

[0086]

[0087]

[0088] It can be seen from the test results of the examples and comparative examples that the acid value of the gel-like prepared by the present invention is reduced by 13% to 60%.

[0089] From the test and analysis data of the products of the present invention from Example 1 to Example 9, it can be seen that as the proportion of modifier addition increases, the shelf life becomes more and more unstable. When the proportion exceeds 20%, the shelf life is less than 18 months, which cannot meet the shelf life requirements of Lekena gum; as the proportion of modifier addition increases, the viscosity, anti-sagging performance, initial adhesion performance, and water resistance are all improved, while the acid value is reduced. Therefore, considering comprehensively, the amount of modifier added is 5% to 20% of the mass of the modified Lekena gum as the best proportion. Users can choose products with different addition ratios according to different indicator requirements.

Claims

1. A method for preparing modified lekena gum with a long shelf life, characterized in that: The following steps are involved: S1. Color change treatment of Lekna glue: In a dark room without light, put yellow or green Lekna glue in a transparent narrow-necked bottle, fill the bottle with nitrogen, seal it, and let it stand. Place an LED lamp 5 cm to 10 cm away from the narrow-necked bottle, and continuously irradiate it with the LED lamp for 72 h to 78 h to change the appearance color of the Lekna glue to red-purple; move the red-purple Lekna glue out of the dark room, heat it up and stir it, and replace the acidic gas in the dry material with nitrogen at the same time, filter out the precipitate and impurities, and seal it; S2 Preparation of modifier: Set the speed of the homogenizer to 1500r / min~2000r / min, the stirring time to 55min~60min, put the liquid nitrile rubber W2740 into the homogenizer for homogenization until there are no bubbles visible to the naked eye, and then take it out; S3: preparing modified Leche gum: weighing the red-purple Leche gum obtained in step S1, and putting it into a homogenizer; weighing the modifier liquid nitrile rubber W2740 obtained in step S2, the mass of the modifier being 5% to 20% of the mass of the modified Leche gum, and dropping the modifier into the homogenizer; setting the speed of the homogenizer to 200 r / min to 300 r / min, and the stirring time to 160 min to 180 min; The mixture is stirred and mixed thoroughly to obtain modified Lekena gum.

2. The method for preparing the modified lekena gum according to claim 1, characterized in that: When the red-purple lekena gum treated in step S1 is heated and stirred, the material temperature is controlled between 136° C. and 140° C., and the temperature is kept constant for 160 min to 180 min. The heating is stopped, and the material is filtered after cooling.

3. A method for detecting modified lekena gum according to claim 1 or 2, characterized in that , including the following tests: S1 Bond Strength Test When using non-5470 according to Q / LHHJGJ02-2019 standard # When bonding rubber, the degree of damage to the bonding surface is used to indicate the bonding strength: Completely destroy the bonding surface rubber damage area ≥ 80% Damage to the bonding surface rubber damage area 50% to 80% Incomplete destruction of the bonding surface rubber damage area 30% to 50% The damaged area of ​​rubber on the bonding surface is not damaged and is ≤30%; S2 Viscosity Test Anti-sagging performance test: Fix a glass test tube on a slope with a scale and an angle of 20 degrees, fix a zero point at the mouth of the glass test tube, take 0.2ml of glue and drop it at the zero point of the test tube, let the glue drip down naturally, measure the dripping distance and time of the glue, and use the average flow rate to indicate the anti-sagging performance; S3 water resistance test Atomization test: Install a humidifier and a hygrometer in the fume hood, keep the humidity constant for 0.5 hours, and then conduct the bonding strength test in the fume hood, that is, simulate the actual humidity environment to conduct the bonding strength test. The limit humidity value when the bonding strength is ≥4.0MPa is used to represent the water resistance of the actual bonding process; S4 initial adhesion test Initial adhesion test: The bonding specimens are two 5470 pieces with a length of 10 cm and a width of 2.5 cm. # Rubber: clean with ethyl acetate, air-dry for 20 minutes, apply a thin layer of glue, the coating area is 10cm x 2.5cm, air-dry for 30 minutes for the first time and 40 minutes for the second time; when pressing, hit the bonding surface with a hammer three times and measure the peeling force; then quickly press, hit the bonding surface with a hammer three times and measure the re-bonding peeling force.